Analysis and Design of Web-Based Information System for Church Congregations Case Study: Church BNKP Pewarta - Jansen Wiratama; Ririn Ikana Desanti (ULTIMA InfoSys, 2021)
During the COVID-19 pandemic, worship activities at the Church were limited. The lack of preparation and data collection on the congregations who visit to worship regularly every week increases the risk of transmission. It needs to be minimized and anticipated. One effort that can be made to reduce this risk is to collect data on the health condition of the congregation who will attend worship. The data collection process is recorded in writing on the attendance list. This requires an iterative approach to be updated and creates a build-up to the attendance record. In addition, media information about the BNKP Pewarta Church activities is not yet available. To overcome this problem, a congregational data collection information system is needed to store congregation data and provide general information about the BNKP Pewarta Church. In designing this Congregation Data Collection Information System, the design method used is the Web Development Life Cycle (WDLC). This information system website design can store Church congregation data and present general Church information.